Impacts of protein quantity and distribution on body composition - Layman, Donald K. (Frontiers in Nutrition, 2024)
The importance of meal distribution of dietary protein to optimize muscle mass and body remains unclear, and the findings are intertwined with age, physical activity, and the total quantity and quality of protein consumed. The concept of meal distribution evolved from multiple discoveries about regulating protein synthesis in skeletal muscle. The most significant was the discovery of the role of the branched-chain amino acid leucine as a metabolic signal to initiate a post-meal anabolic period of muscle protein synthesis (MPS) in older adults. Aging is often characterized by loss of muscle mass and function associated with a decline in protein synthesis. The age-related changes in protein synthesis and subsequent muscle atrophy were generally considered inevitable until the discovery of the unique role of leucine for the activation of the mTOR signal complex for the initiation of MPS. Clinical studies demonstrated that older adults (>60 years) require meals with at least 2.8 g of leucine ( 30 g of protein) to stimulate MPS. This meal requirement for leucine is not observed in younger adults (<30 years), who produce a nearly linear response of MPS in proportion to the protein content of a meal. These findings suggest that while the efficiency of dietary protein to stimulate MPS declines with aging, the capacity for MPS to respond is maintained if a meal provides adequate protein. While the meal response of MPS to total protein and leucine is established, the long-term impact on muscle mass and body composition remains less clear, at least in part, because the rate of change in muscle mass with aging is small. Because direct diet studies for meal distribution during aging are impractical, research groups have applied meal distribution and the leucine threshold to protein-sparing concepts during acute catabolic conditions such as weight loss. These studies demonstrate enhanced MPS at the first meal after an overnight fast and net sparing of lean body mass during weight loss. While the anabolic benefits of increased protein at the first meal to stimulate MPS are clear, the benefits to long-term changes in muscle mass and body composition in aging adults remain speculative.